Contactless electroreflectance study of the surface potential barrier in n-type and p-type InAlAs van Hoof structures lattice matched to InP. (4th May 2018) - Tolloczko, A; Kopaczek, J; Szukiewicz, R; Gocalińska, A; Pelucchi, E; Hommel, D; Kudrawiec, R
Abstract: N -type and p -type In0.52 Al0.48 As van Hoof structures with various thicknesses of undoped In0.52 Al0.48 As layer (30, 60, 90, and 120 nm) were grown using metal–organic vapor phase epitaxy on InP substrates and studied per their contactless electroreflectance (CER) at room temperature. InAlAs bandgap related CER resonance followed by a strong Franz–Keldysh oscillation (FKO) of various period was observed clearly in both structures. The period of this oscillation decreased with decreasing thickness of the undoped In0.52 Al0.48 As layer, and was slightly narrower for p -type structures. The FKO period analysis indicates that the Fermi level is pinned 0.73 ± 0.02 eV below the conduction band at In0.52 Al0.48 As surface. This pinning was attributed to surface reconstruction combined with the adsorption of oxygen and carbon atoms (in consequence of air exposure) which were detected on the In0.52 Al0.48 As surface by x-ray photoelectron spectroscopy. Also, CER measurements repeated one year after the sample growth show that the process of InAlAs oxidation in laboratory ambient conditions is negligible, and thus that this alloy can be used as a protective cap layer in InP-based heterostructures.